Influence of nutrition with leachate based on compost from vegetable waste on the physical, chemical, and biological characteristics of radish (Raphanus sativus L.) - D. D. Cruz Nieto; N. E. Muguruza Crispín; E. T. Castañeda Chirre; J. U. Romero Menacho; J. V. Nunja García; M. C. Saucedo López; J. C. Cabanillas Sulca; C. P. Alvarez Quinteros; C. F. Goñy Ameri; C. M. Caira Mamani; M. N. Morales Alberto; G. P. Lacherre Rodriguez; et al. (Brazilian Journal of Biology)
Abstract The economic instability in Peru was influenced by the post-pandemic period, the war between Russia and Ukraine, and the geopolitical confrontation between the United States and China, which caused an increase in fertilizer prices. The reason why the influence of nutrition with leachate based on compost from vegetable waste (LBCVW) on the physical, chemical, and biological characteristics of radish was investigated. The objective was to analyze the influence of foliar nutrition with LBCVW on the physical, chemical, and biological characteristics of the radish. It was based on applied research with an experimental approach, so the Completely Randomized Block Design statistical model was used, which consisted of 3 blocks and 5 treatments: T1 with 0, T2 with 2, T3 with 3, T4 with 4, and T5 with 5 liters of LBCVW/200 liters of water, and the application was made 14 and 21 days after sowing. Once the data on total plant length, plant weight, commercial yield, and equatorial diameter were obtained, they were processed using analysis of variance and Duncan's test. The concentration of nutrients (nitrogen, potassium, phosphorus, calcium, magnesium, sulfur, molybdenum, iron, manganese, copper, zinc, boron, chlorides, and sodium), the starch percentage, the stomatal density in leaves, and the profitability were determined. The results determined that T5 stood out in total plant length with 40.26 cm, plant weight with 126.32 g, commercial yield with 39.445 t/ha, and equatorial diameter with 4.72 cm. In stomatal density with 586 stomata/mm2 and profitability with 338.6%, and T2 in nutrient concentration such as magnesium, molybdenum, iron, manganese, boron, and starch percentage with 4.55%. It concludes that T5 stood out for its concentration of phosphorus and calcium, higher stomatal density, and lower starch percentage in the leaves. These characteristics influenced the optimization of biochemical reactions such as transpiration, photosynthesis, and the formation and translocation of carbohydrates towards the reserve (bulb), among others. As a result, greater resistance to nutritional and environmental stress was evidenced, achieving a higher yield of 39.445 t/ha, which represents a 24.54% increase compared to T1.